The consequences of strabismus and the benefits of adult strabismus surgery - Astle, Andrew T.; Foulsham, Thomas; McGraw, Paul V. (College of Optometrists, 2016)
Strabismus has a negative impact on patients’ lives regardless of their age. Factors such as self-esteem, relationships with others, education and the ability to find employment may all be negatively affected by strabismus. It is possible to correct strabismus in adulthood successfully; the chances of achieving good ocular alignment are high and the risks of intractable diplopia low. Successful surgery to realign the visual axes can improve visual function, and offer psychosocial benefits that ultimately improve quality of life. The potential benefits of strabismus surgery should be discussed with patients, regardless of their age or the age of onset of strabismus. This article reviews the impact of strabismus, focusing on the psychosocial consequences of the condition, of which many optometrists may be less aware.